2000
DOI: 10.1046/j.1365-2699.2000.00382.x
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories to extinction: spatial dynamics of the contraction of geographical ranges

Abstract: Aim We examined the range contraction of 309 declining species of animals and plants to determine if the contraction dynamics better matched predictions based on the demographic characteristics of historical populations (demographic hypothesis) or based on the contagion‐like spread of extinction forces (contagion hypothesis). Location Species included in the analysis came from all biogeographic regions. Methods We obtained range maps for 309 species from literature or through personal correspondence with aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
207
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(215 citation statements)
references
References 36 publications
8
207
0
Order By: Relevance
“…They are not. The results presented by Channell & Lomolino (2000) are significant precisely because they suggest that factors other than the development of human-specific antipredator behaviours have insulated African faunas against mechanisms driving extinctions elsewhere. And there are many alternative possibilities because Africa is unique in many respects, including greater available habitat area, greater long-term climatic stability, greater equatorial exposure and extraordinary mammalian diversity (Ambrose 1998, Berger 2000.…”
Section: Naivet6mentioning
confidence: 91%
See 1 more Smart Citation
“…They are not. The results presented by Channell & Lomolino (2000) are significant precisely because they suggest that factors other than the development of human-specific antipredator behaviours have insulated African faunas against mechanisms driving extinctions elsewhere. And there are many alternative possibilities because Africa is unique in many respects, including greater available habitat area, greater long-term climatic stability, greater equatorial exposure and extraordinary mammalian diversity (Ambrose 1998, Berger 2000.…”
Section: Naivet6mentioning
confidence: 91%
“…Interestingly, it appears that the dynamics of species undergoing range contraction in present-day Africa are unique, but not restricted to large species that are hunted by humans. Channell & Lomolino (2000) have argued that a singular pattern of contraction extends to a wide range of extant African species: large and small, avian and mammalian, terrestrial and volant. These authors invoke Martin's (1984) concept of coevolution with humans to account for the unique response of African taxa.…”
Section: Naivet6mentioning
confidence: 99%
“…To complicate the issue further, Channell & Lomolino (2000) have undertaken analyses of 309 declining species, using historical data, and have found that the predominant pattern is consistent with the 'contagion hypothesis' of range collapse, i.e. the extinction process first impacts a peripheral population, but then moves to drive more central populations to extinction, so that the last populations to persist are to be found (perhaps in isolates) towards a point on the historic range margin.…”
Section: Integrating Pattern and Processmentioning
confidence: 99%
“…In contrast to results from previous studies, we found strong support for greater vulnerability of edge populations relative to those located near the core of the range. Our analysis differed in three important ways from past studies that have found that edge populations are more likely to persist than core populations (6,25). Unlike past studies, we controlled for threat levels, protected areas, and spatial autocorrelation, which should lead to more robust inference.…”
Section: A Jubatus (As) (Ce) P Tigris (E) P Leo (V) a Jubatus (Amentioning
confidence: 99%